PENGARUH PENERAPAN STRATEGI THINK TALK WRITE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNKASI (TIK) DI KELAS X SMA N 1 LEMBAH GUMANTI - oktarina, rahmi - (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2017)
This research is motivated by the lack of interest, motivation and creativity of students, especially during theory lessons take place, such as the lack of a role in the learning process and the learning system is still dominated by the teacher. The method used in this study is quasy experiment. The population is class X SMA Negeri 1 Valley Gumanti totaling 207 people. The sampling technique used was purposive sampling. X4 grade students an experimental class and X6 grade students as a control group. The data collection technique is using achievement test, the data processed by t test (t-test). Based on the research results. The calculation result obtained t t-test of 2.56, while the level of trust in 0:05 Ttable 2,000, so that t> t table. Based on these data, it is known that there is a significant difference to the learning outcomes of students use learning strategies Think Talk Writedaripada using conventional learning strategies. Thus, it can be concluded that the application of learning strategies Think Talk Write affect student learning outcomes in class X SMA Negeri 1 Gumanti.